Experimental Investigation Monitoring the Saturated Line of Slope Based on Distributed Optical Fiber Temperature System - Feng Li; Weixing Qin; Huiren Hu (Advances in Materials Science and Engineering)
The position of the saturated line is an important basis for evaluating the stability of the slope, and the traditional sensors cannot be monitored for a long time because of poor durability and anti-interference. A method for measuring the saturated line with distributed optical fiber temperature measurement technology was proposed, and the one-dimensional and two-dimensional model experiments of measuring the saturated line at three kinds of electron flow (5 A, 10 A, and 15 A) were conducted, and their measuring data were carefully analyzed. The results showed the three stages of the optical fiber temperature difference with time: sudden-rising, fast-rising, and slow-rising. The temperature rising rate and stable temperature difference at the position of the saturated line are between saturated soil and unsaturated soil. The fiber optic temperature increases with the increment of heating electron flow, which also demonstrates stability and repeatability.